Approche historique de l’agriculture urbaine au Dahomey (Bénin) - Dominique Juhé-Beaulaton (Revue d'ethnoécologie)
The history of the agriculture in the cities of the Gulf of Guinea remains this day little explored. The narratives of European travelers and the oral information collected during inquiries allows to know the place and the evolution of plants cultivated in urban zones since the seventeenth century while questioning the notion of « city ». Based on examples from the ancient kingdom of Dahomey (Abomey, Cana, Ouidah in the south of the present Benin), written historical sources tell the organization of space inhabited by distinguishing different functions according to cities around trade or political administration while showing comparable farm. Cities appear at the same time as places of agricultural innovation and preservation of certain plants. The first contacts with the Europeans (residents of forts and trading posts, Christian missionaries) promoted the development of a truck-farming agriculture; then, the colonial administration contributed strongly to rethink the city and agriculture by creating agricultural stations and a new town planning. However, cultures always remained present in cities, in periphery or in the interstitial spaces and both « models », premises(place) and European, could coexist without competing.